ANALISIS PERSEDIAAN BAHAN BAKU PT HAKAASTON MENGGUNAKAN METODE CONTINOUS REVIEW SYSTEM - Meirizha, St.Nova; Farhan, Muhammad (Fakultas Teknik UMRI, 2022)
Inventory control is a guarantee that the material to be used in the process must always be available at the minimum possible cost. PT HAKAASTON Sei Langsat is engaged in manufacturing asphalt concrete with asphalt and river stone which has not optimal inventory management, which is characterized by a shortage of raw materials when carrying out the production process and resulting in delays in fulfilling consumer demand. With this problem, a research on raw material inventory was conducted using the continuous review system method which aims to control raw material inventory better and optimally. After conducting analysis and calculations using a continuous review system, the optimal number of orders for asphalt is 44,037 Kg and river stone is 23,259 Kg, asphalt reorder point value is 22,665 Kg and river stone is 1,317,611 Kg, asphalt safety stock is 12,048 Kg and stone times, which is 719,394 Kg, while the total cost of inventory using the continuous review system method is Rp. 4,297,432,432, which is smaller than the total cost based on company policy, which is Rp. 5,408,267,366, and savings of Rp. 1,110,834,934 or 21%.